Upaya Meningkatkan Hasil Belajar Melalui Model Metode Eksperimen Dalam Pembelajaran IPAS pada Siswa Kelas IV SD (Penelitian Tindakan Kelas di SDN DAAN Mogot 1) - Mawardi Mawardi; Avika Septiana Hapsari; Sabila Putri Andriani; Virli Ibtisam Naura Azis; Chiqa Arnabila Zahraan (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to improve the learning outcomes of fourth-grade students in science through the application of an experimental learning model on the material of changes in the state of matter. The study used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model which includes the stages of planning, implementation of actions, observation, and reflection. The subjects of the study were 20 fourth-grade students of SDN Daan Mogot 1. The study was conducted in two cycles. Data collection techniques included learning outcome tests, observation of teacher and student activities, and documentation. Data analysis was carried out quantitatively by calculating the average value and percentage of learning completion, and qualitatively through descriptive analysis of the observation results. The results showed that the application of the experimental method was able to improve the quality of the learning process and student learning outcomes. Teacher activity increased from the sufficient category in cycle I to very good in cycle II, while student activity increased from the good category to very good. Increased student activity in observing, discussing, recording results, and drawing conclusions from experiments had a positive impact on understanding the concept of changes in the state of matter. Student learning completion also increased although not all of them reached the classical standard of 80%. Thus, the experimental method is effective in improving the activeness, quality of the learning process, and the science learning outcomes of fourth-grade students. Although material reinforcement and a variety of learning strategies are still needed to optimize learning outcomes.